MUDA WALY AL-KHALIDI (1917-1961): PESANTREN, TARIQAH, AND POLITICS OF RELIGIOUS AUTHORITY IN ACEH - Shadiqin, Sehat Ihsan; Ichwan, Moch Nur; Fuadi, Tuti Marjan; Kim, Najung (Islam Futura, 2025)
This study explores the life and contributions of Muda Waly al-Khalidi (1917–1961), a prominent Acehnese ulama who played a crucial role in shaping Islamic education, Sufi practices, and ulama politics of religious authority in Aceh. Muda Waly was instrumental in advancing the Ahlussunnah wal Jama'ah (Aswaja) theological tradition and propagating the Naqshbandiyya Khalidiyya tariqa.Naqshbandiyah Khalidiyah tariqa. He founded the Darussalam Islamic boarding school (pesantren) in Labuhanhaji, which became a significant center for Islamic learning in Aceh. His efforts also extended into politics through his involvement with Persatuan Tarbiyah Islamiyah (PERTI), a traditionalist Islamic organization countering modernist influences. Using Foucault’s genealogy approach, this study examines the intellectual and religious formation of Muda Waly, tracing his educational lineage in Sumatra and Mecca, his engagement in theological debates, and his role in shaping Aceh’s religious landscape.  I argue that the legacy of Muda Waly al-Khalidi represents an intricate process of knowledge formation and power relations in Aceh’s religious landscape. His establishment of pesantren, propagation of the Naqshbandiyya Khalidiyya Sufi order, and resistance to modernist movements illustrate the genealogical development of religious authority. His contributions demonstrate how religious authoritytraditions are continuously reshaped through negotiation, appropriation, and resistance. Future studies could further explore how his epistemic legacy continues to evolve in response to emerging theological and political contestations in Indonesia.